Restoration of retinal morphology and residual scarring after photocoagulation. (5th April 2013) - Lavinsky, Daniel; Cardillo, Jose A.; Mandel, Yossi; Huie, Philip; Melo, Luiz A.; Farah, Michel E.; Belfort, Rubens; Palanker, Daniel
Abstract. Purpose: To study healing of retinal laser lesions in patients undergoing PRP using SD‐OCT. Methods: Moderate, light and barely visible retinal burns were produced in patients with proliferative diabetic retinopathy scheduled for PRP using 100‐, 20‐ and 10‐ms pulses of 532‐nm laser, with retinal spot sizes of 100, 200 and 400 μm. Lesions were measured with OCT at 1 hr, 1 week, 1, 2, 4, 6, 9 and 12 months. OCT imaging was correlated with histology in a separate study in rabbits. Results: Lesions produced by the standard 100‐ms exposures exhibited steady scarring, with the damage zone stabilized after 2 months. For 400‐ and 200‐μm spots and 100‐ms pulses, the residual scar area at 12 months was approximately 50% of the initial lesion size for moderate, light and barely visible burns. In contrast, lesions produced by shorter exposures demonstrated enhanced restoration of the photoreceptor layer, especially in smaller burns. With 20‐ms pulses, the damage zone decreased to 32%, 24% and 20% for moderate, light and barely visible burns of 400 μm, respectively, and down to 12% for barely visible burns of 200 μm. In the 100‐μm spots, the residual scar area of the moderate 100‐ms burns was 41% of the initial lesion, while barely visible 10‐ms burns contracted to 6% of the initial size. Histological observations in rabbits were useful for proper interpretation of the damage zone boundaries in OCT. Conclusions: Traditional photocoagulation parameters (400 μm, 100 ms and moderate burn) result in a stable scar similar in size to the beam diameter. Restoration of the damaged photoreceptor layer in lighter lesions produced by shorter pulses should allow reducing the common side‐effects of photocoagulation such as scotomata and scarring.